Komersialisasi Pendidikan di Indonesia: Tantangan Bagi Pesantren dalam Mempertahankan Identitas Tradisional - Asiska, Nevi; Dwi Noviani; Paizaludin (TAUJIH: Jurnal Pendidikan Islam, 2024)
The commercialization of education in Indonesia has shifted the paradigm of education, moving the focus from moral and religious learning to a material orientation. Pesantren, as religious-based educational institutions that prioritize traditional values, face significant challenges in maintaining their identity amidst this commercialization. This study aims to understand 1) the impact of commercialization on pesantren, 2) the challenges they face in preserving their traditional character, and 3) the adaptive strategies that can be applied. The research method used is a descriptive qualitative approach with a literature review. The findings show first, that while commercialization provides opportunities to improve educational quality through the adoption of modern curricula and the use of technology, it also risks shifting pesantren’s focus from education based on spiritual and moral values to a material orientation. Second, commercialization also exacerbates social inequality, reduces access for economically disadvantaged groups, and threatens the sustainability of pesantren’s traditional identity. The main challenges faced by pesantren include financial pressure to compete with more established modern educational institutions, changes in the relationship between kyai and santri that are becoming more formal, and the threat to pesantren’s principles of inclusivity and Islamic values. Third, this study suggests that pesantren should maintain a balance between modernization and the preservation of Islamic values by utilizing technology, developing subsidy programs, and strengthening their role as centers for character development. With these strategies, pesantren can survive amidst the pressures of commercialization without losing their identity and core principles.